A simplified method to estimate body growth parameters of the European eel Anguilla anguilla. Issue 3 (6th August 2014) - Melià, P.; Crivelli, A. J.; Durif, C.; Poole, R.; Bevacqua, D.
<x xml:space="preserve">Abstract</x> A simple approach is proposed to fit a body growth model for the European eel Anguilla anguilla to data‐poor case studies. The model is a modified von Bertalanffy curve allowing for delayed sex determination and sexual dimorphism. The proposed procedure provides preliminary estimates of model parameters on the basis of average age and body length of silver eels.